The effectiveness of a golf injury prevention program (GRIPP intervention) compared to the usual warm-up in Dutch golfers: protocol design of a randomized controlled trial - S. Gladdines; A. L. von Gerhardt; E. Verhagen; A. Beumer; D. Eygendaal; GRIPP 9 study collaborative (BMC, 2022)
Abstract Background Sixty million golfers around the world play golf. Golf injuries are most frequently located in the spine, elbow, wrist, hand and shoulder. Those injuries are often seen in golfers with more playing hours and suboptimal swing biomechanics, resulting in overuse injuries. Golfers who do not perform a warm-up or do not warm-up appropriately are more likely to report an injury than those who do. There are several ways to warm-up. It is unclear, which warm-up is most useful for a golfer to perform. Moreover, there is currently no evidence for the effectiveness of a warm-up program for golf injury prevention. We previously have developed the Golf Related Injury Prevention Program (GRIPP) intervention using the Knowledge Transfer Scheme (KTS). We aim to evaluate the effect of the GRIPP intervention on golf-related injuries. The hypothesis is that the GRIPP intervention program will reduce the number of golf-related injuries. Methods and design The GRIPP study is a two-armed randomized controlled trial. Twenty-eight golf clubs with 11 golfers per club will be randomly allocated to the intervention or control group. The intervention group will perform the GRIPP intervention program, and the control group will perform their warm-up as usual. The GRIPP intervention is conducted with the Knowledge Transfer Scheme framework, which is a systematic process to develop an intervention. The intervention consists of 6 exercises with a maximum total of 10 min. The primary outcome is the overall prevalence (%) of golf injuries measured with the Oslo Sports Trauma Research Center (OSTRC-H) questions on health problems every fortnight. The secondary outcome measures will be exposure to golf and compliance to the intervention program. Discussion In other sports warm-up prevention programs are effective in reducing the risk of injuries. There are no randomized trials on golf injury prevention. Therefore, an individual unsupervised golf athlete intervention program is conducted which reflects the daily practice of predominantly unsupervised exposure of amateur golfers. Trial registration The trial is retrospectively (28 October 2021) registered at the Dutch Trial Register: NL9847 ( https://trialsearch.who.int ).